PROMOTION STRATEGY WEDDING PACKAGE (A CASE STUDY AT KARMA KANDARA RESORTS BALI) - Ni Made Bintariani; I Putu Astawa; Lien Darlina (Politeknik Negeri Bali, 2018)
This study aim to determine the promotional strategies applied and the most effective promotional strategy used for wedding package at Karma Kandara Resorts Bali. Collecting data in this study thourgh in dept-interview with the hotel. Data analysis technique used are qualitative descriptive techniques. The result of the research show the implantation of strategy for wedding package at Karma Kandara Resorts Bali such as advertising, personal selling, selling promotion, and publicity. All of the promotional strategies that are used most effectively are Personal Selling for wedding package at Karma Kandara Resorts Bali